Sistema de controle de temperatura usando FPGA - Souza, Alexssandro Braz de (2013)
A temperature controller aims to maintain a constant temperature, within a predetermined range of values. Following these definitions, a digital circuit has been implemented in VHDL that allows the user to interact with FPGAs using discrete components. The tool used is the ISE 12.4, Xilinx, which is a set of programs which operate in an integrated way so that can implement digital systems with a kit of reconfigurable logic. The reconfigurable computing is based on reprogrammable logic devices that can achieve high performance and at the same time providing the flexibility of describing systems at gate level. The system consists of a circuit with discrete components, which has the function of receiving the sensor voltage, interacting with the synthesized VHDL code to perform the control of the temperature.